Karakterisasi Ekstrak Kulit Buah Naga (Hylocereus Sp.) dengan Variasi Konsentrasi Asam Tartarat Sebagai Pewarna Alami Makanan - Fernando, Fernando; Talitha, Zada Agna; Kurniawan, Rahmat (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2025)
Food colorant plays a vital role in the food industry by enhancing visual appeal and shaping consumer perception of product quality. Synthetic food dyes, though commonly used, have been linked to various health concerns such as allergies, hyperactivity in children, and potential carcinogenic risks when consumed above the Acceptable Daily Intake (ADI). Therefore, natural and safe alternatives are needed. This study investigates the potential use of red dragon fruit (Hylocereus sp.) peel extract as a natural food colorant and antioxidant source, using maceration extraction with varying concentrations of tartaric acid (0%, 2%, 4%, 6%, and 8%). Parameters evaluated include physical properties (yield and color intensity), chemical characteristics (pH and total anthocyanins), antioxidant activity, and food processing simulations (thermal stability, pH effects on color, and solvent solubility). The results showed that 4% tartaric acid yielded the highest extraction output, color intensity (absorbance 2.774), highest total anthocyanin, and antioxidant activity (84.06%), with optimal color stability at temperatures up to 40°C and at pH 3. The extract showed excellent solubility in water (97.41%) and 15% ethanol (96.40%), while being insoluble in oil. These results indicate that red dragon fruit peel extract has great potential as a natural dye that not only provides an attractive red color but also functions as a natural antioxidant that is safe and stable under various food processing conditions.